2017
DOI: 10.1016/j.biocon.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with bat mortality at wind energy facilities in the United States

Abstract: Hundreds of thousands of bats are killed annually by colliding with wind turbines in the U.S., yet little is known about factors causing variation in mortality across wind energy facilities. We conducted a quantitative synthesis of bat collision mortality with wind turbines by reviewing 218 North American studies representing 100 wind energy facilities. This data set, the largest compiled for bats to date, provides further support that collision mortality is greatest for migratory treeroosting species (Hoary B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…Our data could not be used to isolate the causes of the trends we observed, and wind energy is not the only source of anthropogenic mortality for our study species (O'Shea et al 2016). Nevertheless, a precautionary approach to bat conservation would minimize mortality of bats at wind turbines (Rydell et al 2010b;Zimmerling & Francis 2016;Thompson et al 2017). Increasing cutin speed of turbines decreased the number of bats killed by turbines in our study, consistent with previous studies (Baerwald et al 2009;Arnett et al 2011bArnett et al , 2016Martin et al 2017), but did not prevent mortality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data could not be used to isolate the causes of the trends we observed, and wind energy is not the only source of anthropogenic mortality for our study species (O'Shea et al 2016). Nevertheless, a precautionary approach to bat conservation would minimize mortality of bats at wind turbines (Rydell et al 2010b;Zimmerling & Francis 2016;Thompson et al 2017). Increasing cutin speed of turbines decreased the number of bats killed by turbines in our study, consistent with previous studies (Baerwald et al 2009;Arnett et al 2011bArnett et al , 2016Martin et al 2017), but did not prevent mortality.…”
Section: Discussionsupporting
confidence: 89%
“…2010b; Zimmerling & Francis 2016; Thompson et al. 2017). Increasing cut‐in speed of turbines decreased the number of bats killed by turbines in our study, consistent with previous studies (Baerwald et al.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (2013) found that mortality probabilities decreased with the distance to eucalyptus forests. Other studies showed that open habitats such as prairies, pastures and croplands triggered fewer collisions than closed habitats such as forests (Bolívar-Cimé et al, 2016;Piorkowski and O'Connell, 2010;Thompson et al, 2017). Piorkowski and O'Connell (2010) found more fatalities in ravine topography than in low topography relief and Santos et al (2013) found that distance to the slope was negatively correlated with mortality risks.…”
Section: Introductionmentioning
confidence: 97%
“…Although there are obvious benefits to applying such strategies, mitigation aimed to offset the ultimate mechanisms leading to bat fatalities would likely be more effective [6]. One of the proposed hypotheses for bat fatalities at wind turbines is that wind energy facilities, or perhaps even individual turbines, are sited in areas that provide resources for bats [7][8][9]. Thus, if bats are in proximity to turbines because of existing resources in the wind energy facility, then pre-construction surveys that aim to identify areas suitable for bats could be used to effectively reduce bat fatalities simply by informing wind turbine siting to avoid such resource-rich areas [9,10].…”
Section: Introductionmentioning
confidence: 99%